Influência de fragilidade e quedas sobre capacidade funcional e marcha de idosos comunitários de Belo Horizonte - Silvia Lanziotti Azevedo da Silva (2011)
Introduction: frailty and falls, separately, cause loss of functional capacity for Activities of Daily Living and changes in spatial and temporal variables of gait and its performance in the elderly. However, it is unclear whether a fall could worsen the consequences of frailty for these adverse outcomes. Objectives: To analyze the consequences of frailty and falls apart and together, for functional capacity in Basic(ADL), Instrumental (IADL) and Advanced (AAVD) activities of daily living and gait performance and changes in spatial and temporal variables of her elders. Methods: A cross-sectional study of a sample of 125 ( 65 years) elderly community selected among 613 elderly who could walk, in which were component of the database Rede Estudos da Fragilidade de Idosos Brasileiros (Rede Fibra) from Belo Horizonte-MG, colected from the same sectional area. Frailty was assessed by the Phenotype of Frailty: unintentional weight loss, low physical activity, exhaustion, weakness and slow walking. The presence of one or two of these items featuring the elderly as pre-frail, three or more of them feature the elderly as frail, not scoring on any item means that the elderly are not-frail. Fall in last 12 months were assessed by direct question. Functional capacity was assessed by the scales Katz (ADL), Lawton (IADL) and Advanced Activities with a structured questionnaire for Rede Fibra. The spatial and temporal variables of gait were recorded after walk in GaitRite System and balance and performance measured by the Dynamic Gait Index (DGI).Results: From 125 elderly assessed, 70.4% were woman, aged 73.77 (±5,65) years old. About 34.4% falls happpened at least one time in the last year, but just two fractures were registred, none of them were on the hip. About 10.4% of the sample was frail, 48.8% pre-frail, and 40.8% no-frail. The functional capacity for ADL and IADL were different among the groups of frailty (p <0.05) but not for falls (p> 0.05). The AAVDs had no significant difference between the scores in both groups (p> 0.05). The spatial and temporal variables of gait velocity, cadence, stride length and time were different between the group of frail elderly and pre-frail and non-frail (p <0.05) but not for falls (p> 0.05). Support base, percentage of balance and support had no significant differences for any group (p> 0.05). DGI showed only the difference between groups divided by frailty and falls (p <0.05). There was no interaction between the effects of falls and frailty in the dependent variables. Conclusions: The falls registered in the sample did not generate serious injuries in the elderly and therefore it has not worsened the deleterious consequences of frailty for ADL and functional capacity for spatial and temporal variables of gait. The DGI assesses the balance and gait challenging of the activities, which can be influenced by the falls, but still no interaction with the effect of frailty.